Análise locacional e espacial da estrutura produtiva do estado do Tocantins - Sousa, Ronildo Borges de (Universidade Federal do Tocantins, 2018)
The present dissertation analyzed the concentration and productive integration within the state of Tocantins, for the period of 2005 and 2015. For that, the regional analysis method and the Exploratory Analysis of Spatial Data (AEDE) method were used. For the first method the location indicators, the locational quotient (QL), the Hirschman Herfindahl concentration index (HHI), the Geographic Association Coefficient (CAG) and the employment multiplier were estimated. For the second, the Moran global (Moran I) and local indicator (LISA) were estimated. For the theoretical basis, the most relevant regional development perspectives were used in the scenario for the study. The results showed that, in the analysis of locational indicators, the sectors that predominate in the majority of municipalities in this state are: public and agricultural administration, plant extraction, hunting and fishing. Regarding the spatial analysis, it was verified through the Moran global index that the sectors that stood out the most for having a more significant spatial autocorrelation in 2005 or in the year 2015 were: industrial utilities, public administration and agriculture, vegetable extraction, hunting and fishing. The LISA statistic showed that the sectors that presented the highest clusters with high QL values were those of public utilities, services and agricultural, vegetable extraction, hunting and fishing, which are the main promoters of the economy of Tocantins. Finally, the main results of this research indicate that the regional development of the municipalities of the state of Tocantins did not present itself homogeneously, neither in time nor in space.